Što je x ako je ln (x ^ 2) + ln (x ^ 3) + 2 = 0?

Što je x ako je ln (x ^ 2) + ln (x ^ 3) + 2 = 0?
Anonim

Odgovor:

# X = korijen (5), (1 / e ^ 2) *

Obrazloženje:

1 "" lnx ^ 2 + lnx ^ 3 + 2 = 0

nekretnine: # Log_bm + = log_bn log_b (m) *

2 "" ln (x ^ 2x ^ 3) + 2 = 0

3 "" ln (x ^ 5) + 2 = 0

Prebaci 2 na drugu stranu.

4 "" ln (x ^ 5) = - 2

5 "" log_e (x ^ 5) = - 2

Pretvori u eksponencijalni oblik.

6 "" hArre ^ -2 = x ^ 5

7 "" korijen (5) (1 / e ^ 2) = korijen (5) (x ^ 5)

8 "" boja (plava) (x = root (5) (1 / e ^ 2))